Treatment of type 2 diabetes mellitus – what is the direction? / Rohana Abdul Ghani. - Abdul Ghani, Rohana (Universiti Teknologi MARA Cawangan Selangor, 2017)
The growing global type 2 diabetes mellitus (T2DM) epidemic has shown no signs of slowing down. The parallel increase in obesity implicates unhealthy diet and sedentary lifestyle as main factors, which are fast becoming a way of life. Environmental and genetic factors have offered alternative perspectives to the diabetes front, although the aging population could be a much simpler explanation. Little has remained constant and a great deal more is being discovered